Evaluation of Bacterial Co-infections of the Respiratory Tract in COVID-19 Patients - Gurung, Kishor; Pant, Prabesh; Pokhrel, Sandeep; Neupane, Dhan Raj; Gurung, Samjhana (Journal of Nepalgunj Medical College, 2021)
Introduction: The coronavirus disease 2019 (COVID-19) pandemic is caused by severe acute respiratory syndrome coronavirus 2. The co-evolution of viral and bacterial respiratory pathogens has created an environment in which a viral infection allows concurrent or secondary bacterial co-infections.Aims: This study was carried out to isolate the different respiratory bacterial pathogens from COVID patients and evaluate their antibiotic sensitivity pattern.Methods: Hospital based descriptive cross sectional study was conducted over a period of between 2nd Jestha to 5th Shrawan 2078 (16th May to 20th July 2021) in Nepalgunj Medical college, Kohalpur during the second wave of COVID-19 in Nepal. The sputum was inoculated onto different culture plates such as Blood Agar (BA) and MacConkey Agar (MA) and incubated at 37 oC. After overnight growth and in Gram staining, different Gram’s positive and negative bacteria were observed. Antibiotic sensitivity test was performed by Kirby-Bauer Disk Diffusion method.Results: Out of 100 sputum samples, 44% positive bacterial growths, majority isolates were Klebsiella spp and Staphylococcus aureus. Overall, the pathogens were mostly sensitive to meropenem followed by colistin, piperacilin/tazobactam respectively.Conclusion: Bacterial co-infection is common in hospitalized patients with SARS-CoV-2.